An implentation of IoT for environmental monitoring and its analysis using k-NN algorithm - Eko Prayitno; Nurul Fahmi; M. Udin Harun Al Rasyid; Amang Sudarsono (Universitas Ahmad Dahlan, 2021)
Environmental monitoring is a process for observing around with various conditions. Recently, internet of things (IoT) and wireless sensor network (WSN) technologies support to solve these problems. In this paper, we implemented a system to monitor environmental conditions using IoT and WSN technology. The data measure is temperature, humidity, carbon monoxide (CO) and carbon dioxide (CO2) sensors. All sensor data will be sent and stored to the cloud through the internet in real-time. We provide applications for monitoring website and mobile phone-based environmental conditions, so users can access wherever and whenever. Furthermore, we also confirm the evaluation of analyst data that usedk-NN method is better than other methods with an accuracy rate of 99.0657%.